A multi-criteria evaluation of container terminal technologies applying the COPRAS-G method - Barysienė, Jurgita (Transport, 2012)
Over the recent years, the usage of containers has dramatically increased; subsequently, port container terminals annually serve more and more intensive flows, which leads to the necessity to find the ways of increasing terminal performance in order to achieve that a growing number of containers would be expeditiously served. The minimization of container handling duration in a terminal would reduce the total transportation time and create preconditions for an increase in the efficiency of the transport chain. The article deals with the above introduced problem on the basis of research on container handling operations applying different technologies when the objective function is the optimization of the container handling cycle that includes assessing the parameters of terminal technical systems and determining the most rational container handling technology. For this purpose, the system of the factors directly influencing the container handling cycle and expert assessment estimating the weight of each factor of the overall handling duration have been determined. With reference to the obtained results and adapted multi-attribute assessment method COPRAS-G, the evaluation of traditional terminal technologies was performed thus determining the most efficient technology under supposed conditions.First Published Online: 21 Dec 2012